2019
DOI: 10.1002/ddr.21564
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Concern: Preventive effect of nerolidol on isoproterenol induced myocardial damage in Wistar rats: Evidences from biochemical and histopathological studies

Abstract: The present study aimed at investigating the protective effects of nerolidol (NRD) against myocardial infarction (MI) induced by isoproterenol (ISO) in Wistar rats. The rats were randomly divided into five groups, each group consisting of six rats. Group I were treated as control rats, group II received NRD (200 mg/kg b.w.) by intragastric intubation for 21 days, group III received ISO (60 mg/kg b.w) subcutaneously (s.c) for two consecutive days on 22nd and 23rd day, group IV and V received NRD (100 and 200 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…Elevated levels of blood cholesterol and its buildup in cardiac tissue are well connected with cardiovascular damage. 49 In the present study, ISOadministered rats showed a significant increase in the levels of TC, TG, and FFA in myocardium and plasma while the levels of PLs increased in the plasma and decreased in heart, which is in line with the previous studies. 15 ISO has been reported to produce stress in the myocardium due to the production of free radicals by its auto-oxidation, which leads to membrane degradation.…”
Section: Discussionsupporting
confidence: 93%
“…Elevated levels of blood cholesterol and its buildup in cardiac tissue are well connected with cardiovascular damage. 49 In the present study, ISOadministered rats showed a significant increase in the levels of TC, TG, and FFA in myocardium and plasma while the levels of PLs increased in the plasma and decreased in heart, which is in line with the previous studies. 15 ISO has been reported to produce stress in the myocardium due to the production of free radicals by its auto-oxidation, which leads to membrane degradation.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we noticed the elevated levels of cTnT and cTnI and the increased activities of the AST, ALT, CK, CK-MB, and LDH in serum of ISO-induced rats; it might be due to the cardiac damage induced by ISO. Our results are consistent with a previous report by Vennila et al, (2010) 31 . ARB pretreatment prevented theses increase in ISO administered rats.…”
Section: Discussionsupporting
confidence: 94%
“…It has been shown to activate antioxidant signaling pathways and attenuate inflammatory and apoptotic signaling pathways, as well as exert cytoprotective properties by improving antioxidant defense [ 29 ] and exerting anti-inflammatory effects [ 23 , 30 , 31 ]. Recently, NERO has been shown to attenuate oxidative stress, inflammation, fibrosis, and apoptosis in cardiotoxicity induced by cyclophosphamide, a chemotherapeutic agent [ 32 ], isoproterenol-induced myocardial infarction [ 33 ], and modulate contractile function of the atrium [ 34 ]. Additionally, NERO has been shown effective as an anticancer agent due to its potential to modulate important molecular targets of cell survival and proliferation [ 35 ], as well as act as a chemosensitizer in cancer cells [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%